(3GdJbOjS OYGA GdSGObjfs
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce s
(3BNQgG (B:s
(3Je GdJbOjS hGdMeO dehdGfG hMOgq s
(3Vef eLehY , JQJjHgG (B: 17s
(3GdSjf JSJNOe HOdG ef GdUGO ai eGOI UOb heTJbGJgG ai gPg GdeLehYIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3dYdgG dYdj Hf MeRI GdOhQRjs
(3QGLY eG bHdg HGdeLehY s
(3bQf GdfSN (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds